2018
DOI: 10.2147/jmdh.s155467
|View full text |Cite
|
Sign up to set email alerts
|

Job strain: a cross-sectional survey of dementia care specialists and other staff in Swedish home care services

Abstract: IntroductionAn increasing number of older persons worldwide live at home with various functional limitations such as dementia. So, home care staff meet older persons with extensive, complex needs. The staff’s well-being is crucial because it can affect the quality of their work, although literature on job strain among home care staff is limited.AimTo describe perceived job strain among home care staff and to examine correlations between job strain, personal factors, and organizational factors.MethodsThe study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Other research showed perceived job strain among staff because of their inability to deliver good enough care. 41 Our study also found that older persons receiving HCS (both PwDs and controls) reported being treated with decreasing levels of dignity and respect over the years from 2016 to 2018. This was especially true for PwDs with poor self-rated health, those who had answered the survey by proxy, and those who were granted more HCS hours.…”
Section: Discussionsupporting
confidence: 66%
“…Other research showed perceived job strain among staff because of their inability to deliver good enough care. 41 Our study also found that older persons receiving HCS (both PwDs and controls) reported being treated with decreasing levels of dignity and respect over the years from 2016 to 2018. This was especially true for PwDs with poor self-rated health, those who had answered the survey by proxy, and those who were granted more HCS hours.…”
Section: Discussionsupporting
confidence: 66%
“…In a previous study, Sandberg, Borell, Edvardsson, Rosenberg, and Boström () found that home care staff, who more frequently served clients with dementia and increased needs, reported higher job strain than other home care staff. While this study reports that clients with cognitive impairment were granted a higher numbers of services and more hours per month, there is no evidence if this greater number of hours per month is equal to the time needed.…”
Section: Discussionmentioning
confidence: 96%
“…One possible reason for their highly rated job strain could be that dementia care specialists rather than other staff worked more extensively with persons with dementia and those with special needs. 12 The dementia care specialists reported higher mean scores on job strain in the study by Sandberg et al 12 compared to nursing home staff from a previous study. 14 It is important to examine job strain reported by staff as previous studies have shown that wellbeing among staff is correlated with the quality of their work and the services provided.…”
Section: Introductionmentioning
confidence: 78%
“…10 Moreover, home care staff often work alone in the older person's home, requiring them to be independent and flexible to accomplish tasks. 11 In a previous study by the research group, 12 dementia care specialists, referring to the nurse aides/ assistants who received dementia care education by taking a web-based course focusing on the guidelines for persons with dementia 13 in the context of home care service, rated job strain significantly higher than other home care staff. One possible reason for their highly rated job strain could be that dementia care specialists rather than other staff worked more extensively with persons with dementia and those with special needs.…”
Section: Introductionmentioning
confidence: 89%